Demographic Characteristics of World Class Jamaican Sprinters - Rachael Irving; Vilma Charlton; Errol Morrison; Aldeam Facey; Oral Buchanan (The Scientific World Journal)
The dominance of Jamaican sprinters in international meets remains largely unexplained. Proposed explanations include demographics and favorable physiological characteristics. The aim of this study was to analyze the demographic characteristics of world class Jamaican sprinters. Questionnaires administered to 120 members of the Jamaican national team and 125 controls elicited information on place of birth, language, ethnicity, and distance and method of travel to school. Athletes were divided into three groups based on athletic disciplines: sprint (s: 100–400 m; n=80), jump and throw (j/t: jump and throw; n=25) and, middle distance (md: 800–3000 m; n=15). Frequency differences between groups were assessed using chi-square tests. Regional or county distribution of sprint differed from that of middle distance (P<0.001) but not from that of jump and throw athletes (P=0.24) and that of controls (P=0.59). Sprint athletes predominately originated from the Surrey county (s = 46%, j/t = 37%, md = 17, C = 53%), whilst middle distance athletes exhibited excess from the Middlesex county (md = 60%). The language distribution of all groups showed uniformity with a predominance of English. A higher proportion of middle distance and jump and throw athletes walked to school (md = 80%, j/t = 52%, s = 10%, and C = 12%) and travelled greater distances to school. In conclusion, Jamaica’s success in sprinting may be related to environmental and social factors.